IMTA-Based Arabic Language Learning Curriculum at LKBA At-Tasniim Yogyakarta - Mitrajati, Kenyo; Musthofa, Tulus; Baroroh, R. Umi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze the Arabic language learning curriculum at the Foreign Language Course Institute (LKBA) At-Tasniim Yogyakarta with the perspective of IMTA' (al-Iţār al-Marji'ī' li Ta'līm al-Lugah al-'Arabiyyah). This research is qualitative with a literature approach. The research data is in the form of an Arabic language learning curriculum applied at the research site with the source of curriculum document data at LKBA At-Tasniim Yogyakarta. The data collection technique uses documentation. Meanwhile, data analysis uses content analysis. The study's results stated that the Arabic language learning curriculum at LKBA At-Tasniim Yogyakarta showed conformity with the level of IMTA's competency standards. This is marked by the goal of student competence at levels 1 to 3 at LKBA At-Tasniim Yogyakarta, which intersects with level 2 of IMTA'. The Arabic language learning curriculum at LKBA At-Tasniim Yogyakarta is designed to pay attention to gradually developing students' language skills from level 1 to level 3. In this case, there is a significant influence and slice with the level 2 IMTA level.